The impact of the COVID‐19 pandemic on glycaemic control in people with diabetes: A systematic review and meta‐analysis. Issue 9 (20th June 2022) - O'Mahoney, Lauren L.; Highton, Patrick J.; Kudlek, Laura; Morgan, Jessica; Lynch, Rosie; Schofield, Ella; Sreejith, Nayanika; Kapur, Ajay; Otunla, Afolarin; Kerneis, Sven; James, Olivia; Rees, Karen; et al.
Abstract: Aim: To identify, appraise and synthesize the available evidence on the impact of the coronavirus disease 2019 (COVID‐19) pandemic and lockdown (LD) on glycaemic control in people with diabetes. Materials and Methods: We searched multiple databases up to 2 February 2021 for studies reporting HbA1c, time in range (TIR), average or fasting glucose, severe hypoglycaemia and diabetic ketoacidosis. Data were pooled using random effects meta‐analysis and are presented as mean difference (MD) with 95% confidence intervals (CI). This review was preregistered on PROSPERO (CRD42020179319). Results: We include 59 studies; 44 (n = 15 464) were included in quantitative syntheses and 15 were narratively synthesized. Pooled data were grouped by diabetes type. Results from 28 studies (n = 5048 type 1 diabetes [T1D] and combined diabetes participants) showed that TIR increased during LD compared with before LD (MD 2.74%, 95% CI 1.80% to 3.69%). Data from 10 studies (n = 1294 T1D participants) showed that TIR increased after LD compared with before LD (MD 5.14%, 95% CI 3.12% to 7.16%). Pooled results from 12 studies (n = 4810 T1D and type 2 diabetes participants) resulted in average glucose decreasing after LD compared with before LD (MD –6.86 mg/dl, 95% CI –8.54 to –5.18). Results for other outcomes, including HbA1c, were not statistically significantly different. Conclusions: The COVID‐19 pandemic was associated with small improvements across multiple outcomes of glycaemic control, although there was insufficient evidence to suggest that this led to changes in HbA1c. Most evidence came from people with access to diabetes technologies in high‐income countries; more research is needed in less advantaged populations.